THE RESULTS OF SURGICAL TREATMENT OF CYSTIC FORMATIONS OF THE BILIARY TRACT IN CHILDREN (Herald of the National Children's Medical Center, 2024)
Cystic transformations of the biliary system are rare types of pathology. There are both extrahepatic and intrahepatic variants of biliary tract malformations. Despite the existence of various theories of the occurrence of these types of malformations, none of them reflects all aspects of the occurrence of pathology. Therefore, the diagnosis and treatment of cystic transformations of the biliary tract in children require special attention from pediatric surgeons.